Menstrual Cup Use in Japanese Women: Subjective Evaluations and Changes in Menstrual Symptoms - Yumi Itaya; Naoko Kuramoto; Yoko Furukawa (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2022)
ABSTRACT   Background: Menstrual cups are a safe and economical alternative to sanitary pads or tampons that also hold equal or smaller quantities of menstrual blood. However, menstrual cups are seldom used by Japanese women. Some Japanese women have recently described on their blogs their experiences of using imported menstrual cups. Purpose:  The purpose of this study is clarify the changes in menstrual symptoms associated with the use of menstrual cups and to explore the availability of menstrual cups among Japanese women. Methods: A mixed method design of both qualitative and quantitative approaches was used. Participants were 22 healthy Japanese midwives with no organic diseases of the uterus or experience of using menstrual cups. The Menstrual Distress Questionnaire (MDQ) was administered before and after intervention with use of menstrual cups, and the presence of any changes in the MDQ score was investigated. Participants used menstrual cups during three menstrual cycles, and recorded the ease of use, degree of comfort, and the presence or absence of pain and problems.                                               Results: The scores of the MDQ completed by 22 Japanese midwives were compared and no significant difference between the two was found, suggesting that the use of a menstrual cup would not have a deteriorating effect on menstrual symptoms. Sixty percent of the feedback from participants who used menstrual cups for the first time was negative, such as Discomfort when using menstrual cup and worry also discomfort regarding hygienic handing of cup. However, over 70% mentioned the physical advantages of menstrual cups over conventional sanitary products such as Reduction in menstruation-related discomfort and Ease of dealing with menstruation. Conclusion: Our study findings suggested that reducing psychological hesitation and decreasing negative impressions, such as anxiety about using it for the first time, are important to promote wider use of menstrual cups by Japanese women.